48.3k views
0 votes
What is the General form of the parabola of (y-3)^2=6(x+8)

1 Answer

5 votes

Answer:

x = 1.5
t^(2) , y = 3 + 2at.

Explanation:

For the parabola
Y^(2) = 4aX ,

General form will be

(X = a
t^(2) , Y = 2at) ,

Thus , for the parabola
(y-3)^(2) = 6(x +8)

Here , a = 1.5 and Y from the above equation should be substituted by y - 3 and X must be substituted by x + 8. After substitution of the same we can use the general equation formula for this parabola also.

Thus , general equation comes out to be :-

x + 8 = 1.5
t^(2) , y - 3 = 2at

x = 1.5
t^(2) , y = 3 + 2at.

User Rap
by
5.6k points